Glacie5 Enterprise: Portable Fridge / Nurul Nadhirah Mohd Elias Zulkifli [et al.] - Mohd Elias Zulkifli, Nurul Nadhirah; Bolhassan, Nazira; Azmi, Azim Azraie; Zainol Azhar Suhaimi, Muhammad Abdullah Fadhil; Mohd Nasir, Noor Ashikin (2016)
Glacie5 Enterprise is a new company operated and based in Malaysia. The name Glacie is derived and taken from the word Latin which means 'ice', which means that our product is related to cooling and bring coolness to people